Tinjauan Kompilasi Hukum Ekonomi Syariah: Jual Beli Barang Aksesoris Mobil di Toko Auto Variasi Prima AC Malang - Elsa Amanatul Barokah (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This research aims to know the buying and selling of goods, car accessories in store Auto Variation Prima AC Malang reviews the Legal Compilation of Islamic Economic. This type of research is the study of law with the empirical approach to the conceptual approach. Methods of collecting primary data obtained from direct interviews, secondary data collection is obtained from the related literature. Analysis of the method used is descriptive analysis method. From the results of research conducted showstransaction that buy sell car accessories at auto variation Prima AC Malang of the unfortunate gaffe in a sighting of khiyar system applied in the buying and selling of goods, there is an element of the obscurity of the seller in mentioned the quality of the goods to be purchased in bai istishna ' and does not fit between the quality of the ordered goods to the ones described by the seller. In the compilation of Economic Law of the sharia article 239 paragraph 1 that the parties who feel cheated in the sale and purchase contract may cancel the sale